The Influence of Course Format, Student Characteristics, and Perceived Teacher Communication and Behavior on Instructional Outcomes Before and During the COVID-19 Pandemic - Elizabeth E. Graham; Heather L. Walter; Tang Tang (Central States Communication Association, 2022)
Two studies examined instructional format (intact vs. hybrid and remote vs. online), classroom climate, student characteristics (engagement and communication apprehension), perceived teacher communication and behavior (teacher competence, clarity, caring), and their influence on instructional outcomes, including cognitive learning, communication satisfaction, and intent to persist in college pre-pandemic and during the pandemic. The findings highlight the important role teacher characteristics (caring, clarity, competence) played in instructional outcomes. This study also revealed that high levels of engagement signals students' willingness to participate in the learning process. Students are a driving force in their own cognitive learning, communication satisfaction, and intent to persist in college. No statistically significant differences were found in instructional outcomes across various instructional formats.